2017
DOI: 10.1007/s10389-017-0809-0
|View full text |Cite
|
Sign up to set email alerts
|

Classmate characteristics, class composition and children’s perceived classroom climate

Abstract: Aim A beneficial classroom climate is vital for school achievements, health, well-being, and school satisfaction. However, there is little knowledge as to how the classmate characteristics and class composition are related to the level of a perceived messy and disorderly classroom climate and whether the estimated relationships vary between different groups of children. The aim of the study was to explore the relationship between classmate characteristics as well as class composition and children's perceived c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 20 publications
(21 reference statements)
1
11
0
4
Order By: Relevance
“…Results of further analyses gave evidence for a gender effect indicating that girls perceive the CBC more positive than boys. This is in line with Koth, Bradshaw and Leaf (2008), but contrary to the study of Persson and Svensson (2017) as well as to the study of Sortkaer and Reimer (2018). For students with SEN, it was shown that they experience a less positive CBC.…”
Section: Discussionsupporting
confidence: 49%
“…Results of further analyses gave evidence for a gender effect indicating that girls perceive the CBC more positive than boys. This is in line with Koth, Bradshaw and Leaf (2008), but contrary to the study of Persson and Svensson (2017) as well as to the study of Sortkaer and Reimer (2018). For students with SEN, it was shown that they experience a less positive CBC.…”
Section: Discussionsupporting
confidence: 49%
“…A number of structural changes took place in the Swedish school system in the early 1990s, which may have contributed to a loss of equity and diversity between schools and may be associated with classroom disorder . In our study, we investigated whether the school‐level proportions of students with a low/average socioeconomic and immigration background were associated with internalizing problems.…”
Section: Discussionmentioning
confidence: 99%
“…Decreasing equity and diversity in Swedish classrooms may also be associated with adolescents' internalizing problems. Because schools with lower socioeconomic conditions and higher proportions of students with an immigration background may have fewer resources, lower‐quality teachers, and the demands on teachers may be greater, these factors also may be associated with classroom disorder, and therefore, may moderate the association between classroom disorder and internalizing problems.…”
mentioning
confidence: 99%
“…To operationalize class-level work avoidance goals, we aggregated students’ responses to the work avoidance goal items and used this as a between-class factor. Aggregating classmates’ characteristics and using this as a between-level variable has been used in past studies that examined the role of classmate characteristics more broadly (Bifulco et al 2011 ; Chiu et al 2017 ; Persson and Svensson 2017 ) and social contagion more specifically (Bakker et al 2006 ; King 2019 ; King and Datu 2017 ).…”
Section: Methodsmentioning
confidence: 99%